2020
DOI: 10.1093/pm/pnaa094
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Neural Microstructure Abnormalities in Type I Chiari Malformation: Associations Among Fiber Tract Integrity, Pain, and Cognitive Dysfunction

Abstract: Background Previous case–control investigations of type I Chiari malformation (CMI) have reported cognitive deficits and microstructural white matter abnormalities, as measured by diffusion tensor imaging (DTI). CMI is also typically associated with pain, including occipital headache, but the relationship between pain symptoms and microstructure is not known. Methods Eighteen female CMI patients and 18 adult age- and educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…Pediatric ICTE subjects were also found to have a ~3mm shortening of the distance from the McRae line to these hindbrain structures, implying a similar type of hindbrain sagging as seen in adult CMI. However, the clivus bone in adult CMI has also been found to be signi cantly shorter compared to controls, with a larger reduction in men than women (5.4 vs. 3 mm, respectively) [29,31,37]. In the present study, the differences in clivus length between ICTE and controls were not as dramatic (1.15 and 2.15 mm, for females and males, respectively), with only the male difference reaching statistical signi cance.…”
Section: Pcf Structure Heightscontrasting
confidence: 48%
See 4 more Smart Citations
“…Pediatric ICTE subjects were also found to have a ~3mm shortening of the distance from the McRae line to these hindbrain structures, implying a similar type of hindbrain sagging as seen in adult CMI. However, the clivus bone in adult CMI has also been found to be signi cantly shorter compared to controls, with a larger reduction in men than women (5.4 vs. 3 mm, respectively) [29,31,37]. In the present study, the differences in clivus length between ICTE and controls were not as dramatic (1.15 and 2.15 mm, for females and males, respectively), with only the male difference reaching statistical signi cance.…”
Section: Pcf Structure Heightscontrasting
confidence: 48%
“…The present pediatric results were compared with adult CMI PCF morphometrics reported previously [31,36,37]. Speci cally, Houston et al looked at >115 adult female CMI subjects compared to matched controls and found 14 signi cant differences they grouped as PCF structure heights, clivus angulation, and odontoid process irregularities [31,36].…”
Section: Pcf Morphometricsmentioning
confidence: 74%
See 3 more Smart Citations